Characterization of the in-situ stress on the Horda platform – A study from the Northern Lights Eos well. (February 2022) - Thompson, Nicholas; Andrews, Jamie Stuart; Wu, Long; Meneguolo, Renata
Highlights: Novel summary of the more complex mechanical observations from the Eos CO2 well. Complex well observations, forcing creative thinking and increased understanding. In situ stress variation observations at well and regional level. Mineralogical changes as a mechanism for in situ stress variation. Regional observations of high interest regarding CCS industry development. Abstract: The Northern Lights project represents a significant step forward in development of an effective and commercially viable CO2 transport and storage solution, providing a flexible and low-cost infrastructure solution for multisource industrial decarbonization. The NO 31/5-7 (Eos) well data provided crucial information into the storage reservoir and caprock conditions. This paper focuses on various aspects of the geomechanical characterization, investigating local well observations in relation to regional knowledge to describe not just the in-situ stress conditions for the immediate injection and storage area but also those of the wider region, providing valuable insight for further area geologic storage. Structural characterization and caprock mineralogy are investigated to better understand the in-situ stress measurements from the Eos well. Mineralogical variations are suggested to play a large role in the stress profile in the caprock sealing complex, and therefore on storage and containment potential. These aspects are considered in combination with rock mechanical phenomena for a holistic description of the Eos observations. Furthermore, we discuss how wellbore instabilities observed from image logs are likely caused by prolonged time and temperature conditions during the drilling/openhole data collection phase and can aid us further in constraining the in-situ stress characteristics.